THE EFFECT OF DHIKR THERAPY ON REDUCING PAIN INTENSITY IN POST-CARDIAC CATHETERIZATION PATIENTS IN GRANDMED HOSPITALS LUBUK PAKAM - Hayati, Kardina; Sari Desi Esta Ulina Sitepu; Syatria Wati; Elisa Afifah (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
Data reported by WHO (Word Health Organization) in 2020 shows that the death rate from cardiovascular disease, especially in developing countries, is increasing every year. Cardiac catheterization is an action that has the highest level of accuracy (96% - 99%) for detecting abnormalities in the heart, especially coronary heart disease. Patients who have heart disease often experience chest pain. Spiritual therapy in the form of dhikr is a non-pharmacological therapy that is thought to reduce pain. Quasi-experimental research design using a pre-test and post-test design without any control measures accompanied by an observation sheet which contains a pain level measurement scale (VAS) used in this research. Quota sampling was used in the research by selecting 20 post-cardiac catheterization patients as research respondents. The results of testing the effect of this research used a sample paired T test where the average pre-test difference was 1,250. This showed that there were differences in results before (pre-test) and (post-test). The p-value obtained was .001, which means that there was a significant effect after giving dhikr therapy on reducing pain intensity. It is hoped that this dhikr therapy technique can be used as a nursing intervention so that it can reduce the pain felt by patients.